2014
DOI: 10.1128/aem.00088-14
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Change in the Abundances of Specific Bacterioplankton Groups Is Consistent across Different Nutrient-Enriched Habitats in Crete

Abstract: A common source of disturbance for coastal aquatic habitats is nutrient enrichment through anthropogenic activities. Although the water column bacterioplankton communities in these environments have been characterized in some cases, changes in ␣-diversity and/or the abundances of specific taxonomic groups across enriched habitats remain unclear. Here, we investigated the bacterial community changes at three different nutrient-enriched and adjacent undisturbed habitats along the north coast of Crete, Greece: a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 74 publications
4
32
1
1
Order By: Relevance
“…cluster, correlation, and taxonomic analysis) at the class, order, and OTU levels. Group P1 was mainly characterized by the dominance of SAR11 representatives, as shown in previous studies [3,14,15,38]. However, to the best of our knowledge, SAR11 surface community dynamics have only been examined in a seasonal study once before using pyrosequencing [15].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…cluster, correlation, and taxonomic analysis) at the class, order, and OTU levels. Group P1 was mainly characterized by the dominance of SAR11 representatives, as shown in previous studies [3,14,15,38]. However, to the best of our knowledge, SAR11 surface community dynamics have only been examined in a seasonal study once before using pyrosequencing [15].…”
Section: Discussionmentioning
confidence: 88%
“…According to Gilbert et al [15], SAR11 follows nutrient enrichment and dominates in winter, while it seems to decrease in high chlorophyll a and DOC concentrations [15]. In another study across different nutrient-enriched habitats on the north coast of Crete (GR), pyrosequencing highlighted an increase of SAR11 with decreasing DOC concentration and chlorophyll a fluorescence [14]. However, Eiler et al [13] and Tada et al [47] have observed an increase in SAR11 during diatom blooms and in high chlorophyll a concentrations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…They can be used as an indicator of nitrogen or phosphorus deficiency. Alteromonadaceae is a bacterial family that contains many genera that belong to bacterioplankton (Fodelianakis et al 2014) and can resist low temperatures (Ivanova et al 2004). Citrobacter, the last group that was characterized for this group of whitefish eggs, are ubiquitous bacteria that contain many species that may use citrate as a sole carbon source (Madigan et al 2010).…”
Section: Properties Of Whitefish Egg-associated Bacteriamentioning
confidence: 99%
“…DNA extraction was performed according to Massana et al (1997) with some modifications, as described in Fodelianakis et al (2014b). DNA yield was quantified by the use of a spectrophotometer (NanoDrop Technologies, Wilmington, USA).…”
Section: Dna Extraction Pcr and Dggementioning
confidence: 99%